ALEXANDER FEINBERG IS AN UZBEK AND RUSSIAN POET (Ustozlar uchun, 2025)
Alexander Feinberg is undoubtedly one of the brightest stars in the sky of Uzbekistan's poets. His work is very colorful. Feinberg's work often reflected his dual heritage, blending Uzbek and Russian cultural influences. His contributions to literature earned him recognition and respect in both Uzbekistan and Russia, and he remains a notable figure in the literary traditions of both countries.